Calcific Aortic Stenosis—A Review on Acquired Mechanisms of the Disease and Treatments - Zebhi, Banafsheh; Lazkani, Mohamad; Bark, David (Frontiers in Cardiovascular Medicine, 2021)
Calcific aortic stenosis is a progressive disease that has become more prevalent in recent decades. Despite advances in research to uncover underlying biomechanisms, and development of new generations of prosthetic valves and replacement techniques, management of calcific aortic stenosis still comes with unresolved complications. In this review, we highlight underlying molecular mechanisms of acquired aortic stenosis calcification in relation to hemodynamics, complications related to the disease, diagnostic methods, and evolving treatment practices for calcific aortic stenosis.